2012
DOI: 10.1099/jmm.0.034124-0
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitors of biofilm formation in laboratory and clinical isolates of Candida albicans

Abstract: Candida albicans cells have the ability to form biofilms on biotic and abiotic surfaces, such as indwelling medical devices. C. albicans cells can interconvert between budded and hyphal growth forms, herein termed the budded-to-hyphal transition (BHT), which is important for the formation of mature biofilms. Previous work identified 23 small organic molecules that could inhibit the BHT but did not affect C. albicans cell viability or budded cell growth. These BHT inhibitors were proposed to inhibit multiple si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…More recently, and using similar HTS techniques, this same group identified 2-adamantanamine (AC17) as a chemosensitizer and potentiator of another azole antifungal, miconazole (60). The Johnson group screened for inhibitors of the budded-to-hyphal-form transition in C. albicans ; the identified inhibitors likely inhibit multiple signalling pathways involved in filamentation, many of which also regulate biofilm formation (61, 62). They subsequently reported that three of these inhibitors, buhytrinA, ETYA and CGP-37157, were capable of inhibiting C. albicans biofilm formation, although the biofilm-inhibitory activity varied among different clinical isolates (62).…”
Section: Development Of Novel Strategies and Therapeutics To Combat Amentioning
confidence: 99%
“…More recently, and using similar HTS techniques, this same group identified 2-adamantanamine (AC17) as a chemosensitizer and potentiator of another azole antifungal, miconazole (60). The Johnson group screened for inhibitors of the budded-to-hyphal-form transition in C. albicans ; the identified inhibitors likely inhibit multiple signalling pathways involved in filamentation, many of which also regulate biofilm formation (61, 62). They subsequently reported that three of these inhibitors, buhytrinA, ETYA and CGP-37157, were capable of inhibiting C. albicans biofilm formation, although the biofilm-inhibitory activity varied among different clinical isolates (62).…”
Section: Development Of Novel Strategies and Therapeutics To Combat Amentioning
confidence: 99%
“…Several inhibitors of hyphal formation and biofilm formation by C. albicans have already been reported, including buhytrin A, ETYA, and CGP-37157 (8). Nonetheless, their structures do not provide insights into their potential activity.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation by C. albicans involves a budded-to-hyphal-form transition (BHT). Toenjes et al found that 23 small molecules inhibit C. albicans BHT (6,7) and subsequently identified 3 compounds that are effective against C. albicans biofilm formation: buhytrin A, ETYA, and CGP-37157 (8).…”
Section: Introductionmentioning
confidence: 99%
“…FLC indirectly inhibits ergosterol synthesis by the inhibition of microsomal cytochrome P450, whereas AMB interacts directly with ergosterol in the plasma membrane. Additionally, recent publications (37)(38)(39)(40)(41)(42) have suggested that the antifungal activity of AMB might also be mediated by oxidative damage. …”
Section: Discussionmentioning
confidence: 99%